Rubus kaznowskii (Rosaceae), a new bramble species from south-central Poland - Piotr Kosiński (Pensoft Publishers, 2021)
Based on field research in south-central Poland, supplemented with a review of herbarium materials, we identified a stable bramble biotype with a range large enough (190 km distance between the outermost stands) to be described as a new regional agamic species, Rubus kaznowskii sp.nov. It belongs to the series Subthyrsoidei(sect. Corylifolii). Although R. kaznowskii has a unique combination of features, it can be potentially mistaken for R. gothicus. It differs from the latter species in many aspects, including: pruinose primocanes, denser indumentum of the abaxial leaf surface, and more curved prickles on the petiole. R. kaznowskii has mainly been observed on rusty soils, in habitats of mixed coniferous and mixed broadleaf forests, usually in sunny places, along forest margins and roads, in clearings and roadside thickets.